ANALISIS SUMBANGAN RETRIBUSI PASAR TERHADAP PENDAPATAN ASLI DAERAH (PAD) KABUPATEN MAGELANG TAHUN 2010 – 2017 - Dimas Deka Suryawan; Lorentino Togar Laut; Whinarko Jalunggono (DINAMIC : Directory Journal of Economic, 2019)
This study aims to determine the effect of the general ticket variable, rent a kiosk or kiosk, permission to use rights to the original income of the district of Magelang. It is assumed that the general ticket, kiosk or kiosk variables have a positive and significant effect on regional original income in Magelang Regency. This type of research is quantitative research. Data collection is done by documenting and observing data from time series from 2010 - 2017. Analysis of data using statistical testing with the help of the SPSS program. In analyzing used multiple linear regression analysis techniques, with statistical tests (t test, F test, coefficient of determination (R2). The results of the study showed that the test of the regression coefficient partially (Test t) with α = 5% shows the three variables (general ticket , rental of kiosks or kiosks, permits to use) have a positive and significant effect on the district's original revenues in 2010-2017. The results of the F test with α = 5% indicate that together with the general ticket, kiosk or kiosk variables, rights permit use has a positive and significant effect on the district's original reveue in 2010-2017